Synthesis V-doped ZnO Using Sonication Method - Safitri, Widiya Nur; Prasetyo, Anton; Aini, Nur (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018DO - 10.18860/icgt.v9i1.849, 2019)
ZnO is one of the compounds widely used as a photocatalyst material which has a band gap of about 3.2 eV, as a results this material will work at ultraviolet area. Improvement the photocatalytic properties can be done by doped ZnO with vanadium. In this study, V-doped ZnO was synthesized using sonication method with dopant concentrations is 0%, 1%, 3%, and 5%. X-ray Diffraction (XRD) data showed that ZnO wurtzite was successfully crystalitized in P63mc space group. IR spectra of sample showed the specific vibration mode at ~440 cm-1 which related to the stretching vibration mode of Zn-O.